The Relationship Between Self-Management and Health Behavior of Hypertension Patients in Romana Tanjung Anom Clinic: Self-Management and Health Behavior - Gultom, Stefi Kristina; Novitarum, Lilis; Simanullang, Murni Sari Dewi (INDONESIAN JOURNAL OF HEALTH SCIENCES RESEARCH AND DEVELOPMENT (IJHSRD), 2024)
Background: Health problems in patients at the  Romana Tanjung Anom clinic arise as a result of health behaviors that have a negative impact. Health problems are the result of human behavior in interacting with themselves and their environment, both biological, psychological, socio-cultural, and even political environments. Efforts to overcome health problems are by changing health behavior in self-management. This study aimed to find out whether there is a relationship between self-management and health behaviour behavior of hypertensive patients. Methods: Methods of the research conducted was correlational with a cross-sectional approach, involving 79 respondents.The sampling method employed was purposive sampling.Researchers used the first 2 questionnaires, namely self-management with 40 questions.The second questionnaire is behavior with 17 questions. Questionnaires are filled out and submitted offline or directly at the place of research. This study used bivariate analysis and with statistical tests of spearman rank. Results: The result of the study were obtained  Self-management of hypertensive patients at Romana Tanjung Anom Clinic had good self-management of 47 respondents (59.5%) from 79 respondents. The health behavior of hypertensive patients at Romana Tanjung Anom Clinic in 2023 has good health behavior of 68 respondents (86.1%) from 79 respondents. There is a significant relationship between self-management and health behavior hypertensive patients at Romana Tanjung Anom Clinic in 2023 with p-value=0.019 (p<0.05) and a correlation of 0.264. Conclusion: The conclusion of this study is that there is a significant relationship between self-management and health behavior of hypertensive patients at Romana Tanjung Anom Clinic  and have good health behaviors